2012
DOI: 10.1074/jbc.m112.348730
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structure and IgE Epitopes of Blo t 21, a Major Dust Mite Allergen from Blomia tropicalis

Abstract: Background: Blo t 21 is a paralogue of the group 5 allergen with comparable allergenicity. Results: Blo t 21 has an additional conformational IgE epitope and only a low to moderate cross-reactivity with Blo t 5. Conclusion: Blo t 21 represents a novel group of major allergen in the dust mite Blomia tropicalis. Significance: The structure and IgE epitopes of Blo t 21 allow design of hypoallergen for immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 31 publications
2
39
0
1
Order By: Relevance
“…As Blo t 21 shares over 40% sequence identity with Blo t 5 (Table 2) and the structures of both proteins resemble each other (Fig. 1e, l), it has been hypothesized that Blo t 21 is a paralog of group 5 mite allergens that originated by gene duplication [79]. Despite their similarities, the allergens are not highly cross-reactive.…”
Section: Allergens Of B Tropicalismentioning
confidence: 99%
See 3 more Smart Citations
“…As Blo t 21 shares over 40% sequence identity with Blo t 5 (Table 2) and the structures of both proteins resemble each other (Fig. 1e, l), it has been hypothesized that Blo t 21 is a paralog of group 5 mite allergens that originated by gene duplication [79]. Despite their similarities, the allergens are not highly cross-reactive.…”
Section: Allergens Of B Tropicalismentioning
confidence: 99%
“…k Blo t 19 (2MFJ). l Blo t 21 (2LM9); the depicted residues have been shown to be a part of B-cell epitopes [79]. …”
Section: Allergens Of B Tropicalismentioning
confidence: 99%
See 2 more Smart Citations
“…Gao et al (21) demonstrated that Blo t 21 was not highly cross-reactive to Blo t 5 despite a certain amount of sequence and structural identity, while Weghofer et al (22) showed that Der p 21 exhibited low IgE reactivity to Der p 5, Lep d 5 and Blo t 5 according to tests using sera from Der p 21-sensitized patients. In addition, Blo t 21 was reported to have low to moderate cross-reactivity with Blo t 5, Der p 5 and Der f 21 (24). While multiple studies have focused on Der p 5 and Blo t 5, group-5 and -21 allergens from Dermatophagoides farinae and Tyrophagus putrescentiae, which are the predominant mite species in Korea, have yet to be examined.…”
Section: Introductionmentioning
confidence: 99%